Effect of epigenetics on vitamin D levels: a systematic review until December 2020 - Ali Forouhari; Motahar Heidari-Beni; Shaahin Veisi; Parnian Poursafa; Roya Kelishadi (BMC, 2023)
Abstract Background The association between epigenetic modification of the genes involved in the vitamin D metabolic pathway and vitamin D metabolites' status has been elucidated incompletely. This study aims to review the studies on the mentioned association and create a brighter view of this topic. Methods A systematic literature search was conducted in Medline database (PubMed), Scopus, and Web of Science up to the end of November 2020. Original articles which reported the effect of epigenetic alteration-methylation level or its changes-of genes involved in vitamin D regulation on the vitamin D metabolites serum level or its changes were included. The National Institutes of Health (NIH) checklist was used to assess the quality of included articles. Results Among 2566 records, nine reports were included in the systematic review according to the inclusion and exclusion criteria. Studies discussed the contribution of methylation status of members of the cytochrome P450 family (CYP2R1, CYP27B1, CYP24A1), and Vitamin D Receptor (VDR) genes to vitamin D level variance. CYP2R1 methylation status could regulate the contributing factors affecting the vitamin D serum level and predict response to vitamin D supplementation. Studies revealed that impaired methylation of CYP24A1 occurs in response to an increase in serum level of 25-hydroxyvitamin D (25(OH)D). It is reported that the association between methylation levels of CYP2R1, CYP24A1, and VDR genes and 25(OH)D level is not affected by the methyl-donors bioavailability. Conclusions The epigenetic modification of the vitamin D-related genes could explain the vitamin D levels variation among populations. Large-scale clinical trials in various ethnicities are suggested to find the effect of epigenetics on vitamin D response variation. Registration The systematic review protocol was registered on PROSPERO (registration number: CRD42022306327).